An An Epistemic Coexistence-Based Integrative Pedagogical Model of Islam and Science in Higher Education - Sulaeman, Sulaeman (TA`DIBUNA, 2025)
The relationship between Islam and science remains a strategic focus in Islamic higher education institutions. This study examines the implementation of Nidal Guessoum’s epistemic-ethical coexistence model in enhancing the religious-scientific literacy of students at Muhammadiyah University of Makassar. Using a qualitative-exploratory design, data were collected through interviews, classroom observations, and document analysis, then analyzed thematically. The majority of respondents recognized the importance of integration, although their understanding of it varied. When Islamic values were directly linked with scientific concepts, student participation and critical reflection increased, especially on environmental and technological issues. Furthermore, 74% of students indicated that this approach helped unify rationality and faith. However, the main challenges stemmed from limited interdisciplinary competence among lecturers and inconsistent institutional policy support. Nevertheless, the findings indicate significant opportunities to strengthen religious-scientific literacy through integrative curriculum policies and targeted faculty training. This study affirms that integrating science and religion is not only feasible but also effective in fostering a holistic conceptual and spiritual understanding. The study also recommends longitudinal research to evaluate the long-term impact on students’ scientific and ethical competencies as well as on society at large.